The Development of Learning Model through Video Documentary to Improve Environmental Knowledge of Coastal Residents of Palopo City, Indonesia (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aims to develop the Environmental Learning Model (ELM) by using documentary videos to improve knowledge of coastal residents of Palopo City about mangrove, wastewater, domestic waste, and liveable house. There were two phases used in this research. The first phase examined the concept of the lesson plan, guidedbook, video material, evaluation tests, and answer sheets that were validated by the experts. In the second phase, two reviewers examined the practicality and the effectivity of the learning implementation. The validity result of the guided-book was in very valid category. The lesson plan was in very valid category, and the video material was also in the very valid category. This validation was carried out by educational expert and multimedia expert. Practicality: Two educational reviewers stated the syntax, social system, reactional principle, support system were implemented entirely. Effectivity: The learning result of environmental knowledge in the first trial was in the Medium category (47,5). And in the second trial, it improved to the High category (60,8).So, it can be stated that the development of learning model through documentary videos is valid, practical, and effective to be used in improving environmental knowledge for the coastal resident to avoid bad behaviour.